Treatment of Type II Amiodarone-Induced Thyrotoxicosis by Either Iopanoic Acid or Glucocorticoids: A Prospective, Randomized Study - Bogazzi, Fausto; Bartalena, Luigi; Cosci, Chiara; Brogioni, Sandra; Dell’Unto, Enrica; Grasso, Lucia; Aghini-Lombardi, Fabrizio; Rossi, Giuseppe; Pinchera, Aldo; Braverman, Lewis E.; Martino, Enio (The journal of clinical endocrinology and metabolism, 2003)
Amiodarone-induced thyrotoxicosis (AIT) may occur either in the presence of underlying thyroid disease (type I AIT) or in apparently normal thyroid glands (type II AIT). Type II AIT, a destructive thyroiditis, often favorably responds to glucocorticoids. Iopanoic acid (IopAc) is an iodinated cholecystographic agent that inhibits deiodinase activity and reduces the conversion of T4 toT3. It has recently been reported that cholecystographic agents restore euthyroidism in patients with type II AIT. We describe the results of a prospective randomized study conducted in 12 patients with type II AIT treated with either iopanoic acid (group A, n = 6) or glucocorticoids (group B, n = 6). Serum free T3 levels normalized rapidly in both groups after 7 d, from 0.75 ± 0.20 ng/dl (11.5 ± 3.1 pmol/liter) to 0.46 ± 0.10 ng/d (7.1 ± 1.7 pmol/liter), P < 0.01, and from 0.58 ± 0.10 ng/dl (9.0 ± 1.2 pmol/liter) to 0.34 ± 0.03 ng/dl (5.2 ± 0.5 pmol/liter), P < 0.003, in groups A and B, respectively (P = NS). Serum free T4 levels reduced at 6 months in group B [from 2.70 ± 0.32 ng/dl (35.1 ± 4.1 pmol/liter) to 1.0 ± 0.04 ng/dl (13.4 ± 0.6 pmol/liter), P < 0.0001] but not in group A (from 2.90 ± 0.6 ng/dl (38.0 ± 7.5 pmol/liter) to 2.30 ± 0.4 ng/dl (35.6 ± 6.1 pmol/liter, P = 0.39; P = 0.005 group B vs. group A). All patients in both groups became euthyroid and had their amiodarone-induced destructive thyroiditis cured as defined by normalization of both serum free T4 and free T3 levels, during both drugs therapy. However, patients in group B were cured more rapidly than patients in group A (43 ± 34 d vs. 221 ± 111 d, respectively, P < 0.002). This study shows that, albeit both drugs are effective, glucocorticoids are probably the drug of choice for more rapidly curing type II AIT.